2018
DOI: 10.1097/mao.0000000000001684
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hearing Preservation Outcomes for Small Vestibular Schwannomas: Retrosigmoid Removal Versus Observation

Abstract: Tumor removal should be the first treatment option for patients with small VSs and preserved hearing, especially for young patients with good hearing; retrosigmoid approach is an effective and safe approach for small VSs removal with excellent functional outcomes; better preoperative hearing predicted a higher rate of postoperative hearing preservation; patients without fundal extension were more likely to achieve hearing preservation than those with fundal extension, but no difference had been detected when r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
3
21
1
Order By: Relevance
“…While some studies reported data limited exclusively to tumors completely confined to the IAC without cisternal involvement, others presented data on ''small'' tumors defined as purely intracanalicular or with \15-mm CPA extension. 26,27 In a retrospective study of 94 patients who underwent retrosigmoid resection, HP was 50% for intracanalicular tumors and 29% for tumors with extrameatal extension. 28 Staecker et al compared hearing outcomes between patients who underwent middle cranial fossa and retrosigmoid approaches and reported a HP rate of 47% for intracanalicular tumors, whereas no hearing was preserved for larger tumors with an average size of 1.3 cm.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported data limited exclusively to tumors completely confined to the IAC without cisternal involvement, others presented data on ''small'' tumors defined as purely intracanalicular or with \15-mm CPA extension. 26,27 In a retrospective study of 94 patients who underwent retrosigmoid resection, HP was 50% for intracanalicular tumors and 29% for tumors with extrameatal extension. 28 Staecker et al compared hearing outcomes between patients who underwent middle cranial fossa and retrosigmoid approaches and reported a HP rate of 47% for intracanalicular tumors, whereas no hearing was preserved for larger tumors with an average size of 1.3 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The suboccipital retrosigmoid approach commonly used in the management of lesions of the cerebellopontine angle including vestibular schwannoma, choleostoma, trigeminal neuralgia, and facial spasm (1)(2)(3)(4)(5)(6)(7). It is characterized by a minimal incisions and bone flaps measuring 4 cm and 20 × 25 cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several guidelines and systematic reviews have been published, even recently, which concerned alternative management procedures including wait‐and‐scan (WaS), MSR, or SRS without a high level of evidence owing to the lack of prospective studies and the numerous elements involved in the decision making process, such as the tumor features, presenting symptoms, technique development, and patient willingness 9,10 . To date, the great majority of studies published about long‐term outcomes under different management procedures were less than 10 years 11–13 …”
Section: Introductionmentioning
confidence: 99%